Best Mode of Delivery for Fetal Life-Limiting Conditions. Issue 2 (February 2019) - Cooper, Shontreal; Williams, Nayo S.
Abstract : A 38-year-old woman, gravida 3 para 2, with a history of two prior vaginal deliveries, at 18 weeks of gestation is diagnosed with fetal anencephaly. The patient asks: "May I undergo a scheduled primary cesarean delivery to optimize my baby's chance of survival?" Abstract : Management plans for fetal life-limiting conditions should use the shared decision-making model, especially as it pertains to mode of delivery.